Retrospective analysis for detecting seismic precursors in groundwater argon content - Biagi P. F.; Piccolo R.; Minafra A.; Maggipinto T.; Castellana L.; Molchanov O.; Capozzi V.; Perna G.; Khatkevich Y. M.; Gordeev E. L.; ERMINI, ANITA (Natural Hazards and Earth System Sciences, 2004)
We examined the groundwater Argon content data sampled from 1988 to 2001 at two wells in Kamchatka (Russia) and anomalous increases appeared clearly during June-July 1996. On 21 June, a shallow (I km) earthquake with M=7.1 occurred at a distance less than 250km from the wells and so the previous increases could be related to this earthquake and, in particular, could be considered premonitory anomalies. In order to support this raw interpretation, we analysed the data collected in details. At first we smoothed out the high frequency fluctuations arising from the errors in a single measurement. Next we considered the known external effects on the water of a well that are the slow tectonic re-adjustment processes, the meteorology and the gravity tides and we separated these effects applying band-pass filters to the Argon content raw trends. Then we identified the largest fluctuations in these trends applying the 3 sigma criterion and we found three anomalies in a case and two anomalies in other case. Comparing the time occurrence of the anomalies at the two wells we found out that a coincidence exists only in the case of the premonitory anomalies we are studying. The simultaneous appearance of well definite anomalies in the residual trends of the same parameter at two different sites supports their meaning and the possibility that they are related to some large scale effect, as the occurrence of a strong earthquake. But, other earthquakes similar to the June 1996 event took place during the Argon content measurements time and no anomaly appeared in this content. In the past, some of the authors of this paper studied the Helium content data collected in three natural springs of the Caucasus during seven years. A very similar result, that is the simultaneous appearance of clear premonitory anomalies only on the occasion of a strong (M=7.0) but shallow (2-4 km) earthquake, was obtained. The correspondence with the case of the Caucasus validates the interpretation of the Kamchatkian anomalies as precursors.